Performance of rural development projects by voluntary agencies - Shripathi, K.P. (1995)
"Rural development is an integrated process of sectoral development aiming at increased per capita income and standard of living of rural people. Several international, national and local agencies are involved in this task. The implementation of the rural development programme requires a strong organisation and number of agencies like government and non-government, local, self-help voluntary group working in a coordinated manner. Historically, India's voluntary agencies have provided a series of socio-economic change experiments. Now, they invest a significant amount on rural development activities and they have been specialising in various areas of rural development. Their role has changed from being a mere social institution to that of an advanced economic system. In this changed context, economics has to play its role in determining the appropriateness of voluntary agencies in rural development and application of management techniques in their working assumes importance. In this study an attempt is made to evaluate the working of voluntary agencies with reference to organisation, coordination and delivery system component and to evaluate the impact of their programmes on target groups considering the pre and post-project conditions"
Keywords: Rural development - India